2016
DOI: 10.1186/s13229-016-0109-5
|View full text |Cite
|
Sign up to set email alerts
|

Urinary metabolomics of young Italian autistic children supports abnormal tryptophan and purine metabolism

Abstract: BackgroundAutism spectrum disorder (ASD) is still diagnosed through behavioral observation, due to a lack of laboratory biomarkers, which could greatly aid clinicians in providing earlier and more reliable diagnoses. Metabolomics on human biofluids provides a sensitive tool to identify metabolite profiles potentially usable as biomarkers for ASD. Initial metabolomic studies, analyzing urines and plasma of ASD and control individuals, suggested that autistic patients may share some metabolic abnormalities, desp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
188
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 197 publications
(204 citation statements)
references
References 69 publications
14
188
2
Order By: Relevance
“…Among the 39 ASD-enriched pathways, 17 are from yeast and one of them synthesizes 2-amino-3-carboxymuconate semialdehyde (Table S3), the intermediate to generate an excitotoxin—quinolinic acid—through the subsequent kynurenine pathway. This result is consistent with the previous findings in ASD patients of overproduction of quinolinic acid( 31 ) and overgrowth of yeast in the intestine( 32 ). The consistency of the ASD-associated pathways we identified with previously reported metabolic alterations in ASD supported the reliability of our novel analysis strategy of quasi-paired cohort, and further confirmed the contributions of gut microbial metabolism to hosts.…”
Section: Resultssupporting
confidence: 93%
“…Among the 39 ASD-enriched pathways, 17 are from yeast and one of them synthesizes 2-amino-3-carboxymuconate semialdehyde (Table S3), the intermediate to generate an excitotoxin—quinolinic acid—through the subsequent kynurenine pathway. This result is consistent with the previous findings in ASD patients of overproduction of quinolinic acid( 31 ) and overgrowth of yeast in the intestine( 32 ). The consistency of the ASD-associated pathways we identified with previously reported metabolic alterations in ASD supported the reliability of our novel analysis strategy of quasi-paired cohort, and further confirmed the contributions of gut microbial metabolism to hosts.…”
Section: Resultssupporting
confidence: 93%
“…Croonenberghs and co-workers (53) found lower plasma tryptophan concentrations in 26 autistic subjects (aged 12-18 years) than in normal volunteers. Gevi et al (54) showed differences in TRYCATs including KA, KYN, QA, 5-HT levels, in 30 ASD patients (aged 3-7 years) when compared to controls. There is a partial overlap between both childhood autism and IDD, namely in our study 16 of the 25 IDD patients showed childhood autism and the 9 others not.…”
Section: Discussionmentioning
confidence: 99%
“…These metabolic characteristics correspond to the physiological characteristics during this life stage, high metabolism activity for rapid growth and development demands [4]. Research on children aged from 2-7 years old suggested that pantothenate and CoA biosynthesis, pyrimidine metabolism and vitamin B6 metabolism were signi cantly related to autism spectrum disorder (ASD) [22]. These results highlight the importance for these pathways to maintain homeostasis during preschool.…”
Section: Metabolomic Characteristics During Each Age Stagementioning
confidence: 60%